Balanced SSFP Dixon imaging with banding‐artifact reduction at 3 Tesla. Issue 3 (16th September 2014) - Quist, Brady; Hargreaves, Brian A.; Daniel, Bruce L.; Saranathan, Manojkumar
<x xml:space="preserve">Abstract</x> Purpose To develop a three‐dimensional (3D) balanced steady‐state free‐precession (bSSFP) two‐point Dixon method with banding‐artifact suppression to offer robust high‐resolution 3D bright‐fluid imaging. Methods A complex sum reconstruction that combines phase‐cycled bSSFP images acquired at specific echo times for robust fat/water separation without banding was investigated and compared with a magnitude‐based method. Bloch simulations using both single‐peak and multiple‐peak fat models were performed to predict the performance of these methods for a wide range of echo times and repetition times. The quality and degree of fat/water separation was evaluated in both simulations and using in vivo imaging. Results Simulations predicted that both effective banding‐artifact suppression and substantial improvements in fat/water separation are possible at echo times that are different from conventional echo times, enabling improved spatial resolution. Comparisons between various echo times and repetition times in vivo validated the improved fat/water separation and effective banding‐artifact removal predicted by the simulations. Conclusion The proposed complex sum Dixon 3D bSSFP method is able to effectively separate fat and water at different sets of echo times, while removing banding‐artifacts, providing a fast, high‐resolution, T2‐like sequence without blurring. Magn Reson Med 74:706–715, 2015. © 2014 Wiley Periodicals, Inc.